Pengaruh Variasi Komposisi Bahan Baku Pembuatan Pulp terhadap Kualitas Dan Rendemen Pulp Kraft - Erwan Handoko; Zulfansyah Zulfansyah; Hari Rionaldo; Dimas DP Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The increasing demand of pulp in the world requires sufficient availability of raw materials. To fulfill the raw material supply, it can be established through development of industrial plantations (HTI). Acacia sp and Eucalyptus sp are the types of wood that are prioritized for development in industrial plantations because these species are fast growing species, high timber production, and do not require high living requirements. The study was conducted on a mixture of Acacia crassicarpa and Eucalyptus raw materials with the compositions are 75% Acacia crassicarpa : 25% Eucalyptus (AC:EH-75:25), 50% Acacia crassicarpa : 50% Eucalyptus (AC:EH-50:50)and 25% Acacia crassicarpa :75% Eucalyptus (AC:EH-25:75). Pulping is done by means of a kraft process. The best cooking conditions with kappa number target 17 ± 1 were obtained in the variety of raw materials for 25% Acacia crassicarpa and 75% Eucalyptus (AC:EH-25:75) with active alkali concentration 18%, temperature 165 oC, ratio 1: 4 and H factor 800 with screen pulp yield 50,52%, brightness 36,96% ISO, viscosity 1045 mL/g, and productivity 248,6 kg/m3 where in this variation the composition of the wood used contains more Eucalyptus than Acacia crassicarpa. Eucalyptus wood has a higher density resulting in a higher productivity. Keywords : active alkali, h factor, brightness, viscosity, density